2018
DOI: 10.1021/acsami.7b18362
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Thermoelectric Performance in Na-Doped Pb0.6Sn0.4Te0.95–xSexS0.05 via Breaking the Inversion Symmetry, Band Convergence, and Nanostructuring by Multiple Elements Doping

Abstract: Topological insulators have attracted much interest in topological states of matter featuring unusual electrical conduction behaviors. It has been recently reported that a topological crystalline insulator could exhibit a high thermoelectric performance by breaking its crystal symmetry via chemical doping. Here, we investigate the multiple effects of Na, Se, and S alloying on thermoelectric properties of a topological crystalline insulator PbSnTe. The Na doping is known to be effective for breaking the crystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 35 publications
(82 reference statements)
0
7
0
Order By: Relevance
“…94 The nano-precipitates with coherent or semicoherent interfaces have been widely observed in PbTe-PbQ (Q = Se, S) solid solutions. 61,63,95,96 Interestingly, the shapes and sizes of nano-precipitates in a given thermoelectric system are also sensitive to the processing parameters during synthesizing, such as cooling rate, annealing temperature and annealing time, etc. 53,97 Internal structure designs in PbTe-based thermoelectric materials Most of superior PbTe-based thermoelectric materials are obtained by reducing lattice thermal conductivity through scattering phonons via designing special microstructures.…”
Section: Manipulations On Phonon To Reduce Lattice Thermal Conductivitymentioning
confidence: 99%
See 1 more Smart Citation
“…94 The nano-precipitates with coherent or semicoherent interfaces have been widely observed in PbTe-PbQ (Q = Se, S) solid solutions. 61,63,95,96 Interestingly, the shapes and sizes of nano-precipitates in a given thermoelectric system are also sensitive to the processing parameters during synthesizing, such as cooling rate, annealing temperature and annealing time, etc. 53,97 Internal structure designs in PbTe-based thermoelectric materials Most of superior PbTe-based thermoelectric materials are obtained by reducing lattice thermal conductivity through scattering phonons via designing special microstructures.…”
Section: Manipulations On Phonon To Reduce Lattice Thermal Conductivitymentioning
confidence: 99%
“…At last, a discussion of future possible strategies is proposed to aim at further enhancing the thermoelectric performance in PbTe-based materials. PbTe-Ge:Na, 101 (2) PbTe:(Na, Bi), 102 (3) PbTe-Sn:(Ag, Sb), 103 (4) PbTe-Mn:Na, 104 (5) PbTe-Se:K, 105 (6) PbTe-Ca:Na, 91 (7) PbTe-Cd:Na, 92 (8) PbTe-S:K, 61 (9) PbTe:Na, 106 (10) PbTe:Na (Nano-precipitates), 107 (11) PbTe-Ge, 108 (12) PbTe-Se-S:Na, 109 (13) PbTe-Hg: Na, 110 (14) PbTe:Tl, 64 (15) PbTe-Sn-Se-S: Na, 95 (16) PbTe-Yb:Na, 111 (17) PbTe-Se:Na, 62 (18) PbTe-Mn-Sr:Na, 112 (19) PbTe-Mg:Na, 60 (20) PbTe-Eu:Na, 113 (21) PbTe-Sr:Na, 59 (22) PbTe-S:Na, 63 (23) PbTe-Sr:Na (Non-equilibrium); 53 d peak ZT values as a function of optimized carrier density in n-type PbTe systems: (1) PbTe-Se:Cr, 114 (2) PbTe-Se-S:I, 115 (3) PbTe-NaCl, 116 (4) PbTe-Zn:I, 117 (5) PbTe-Cd:I, 118 (6) PbTe-Sn-Se:I, 119 (7) PbTe-Mg:I, 120 (8) PbTe-Se-S:Cl, 121 (9) PbTe:Cd, …”
Section: Introductionmentioning
confidence: 99%
“…When Sn content increases to 0.40 in Pb 0.6 Sn 0.4 Te , and Sn content to ∼0.23 in Pb 0.77 Sn 0.23 Se, the band gap reaches close to zero, indicating that Se alloying could promote the band inversion of PbTe. During the process of band inversion, approaching topological insulating states, the electronic band structures will become sharper, which can cause a smaller carrier effective mass and a higher carrier mobility. Moreover, nanostructures are expected to be avoided due to complete solubility of Sn and Se in the PbTe matrix, which also could maintain high carrier mobility. In this work, we found that the electronic band inversion (approaching topological insulating states) leads to high-performance n-type PbTe.…”
Section: Introductionmentioning
confidence: 99%
“…All actual metal oxides contain some defects that have a great influence on the properties of materials due to thermal equilibrium and kinetics during the reaction Specifically, the defect structure of cubic crystalline phase can lead to the depletion of the ion loader and the cross diffusion of the elements, that is, the concentration gradient and interaction between the ion defects and the charge carriers …”
Section: Introductionmentioning
confidence: 99%
“…‐ There are many chemical synthesis methods carried out to realize elements doping of materials, for example, Ginting and his co‐workers successfully synthesized Na‐doped Pb 0.6 Sn 0.4 Te 0.95−x Se x S 0.05 by using PbSe and PbS as precursors and mixing with Pb, Te, Sn and Na. They found that Na doping played an important role in breaking the crystalline mirror symmetry of Pb0.6Sn0.4Te . Not long ago, Bao et.…”
Section: Introductionmentioning
confidence: 99%